2004
DOI: 10.2307/4003795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signs in Cattle Grazing High Molybdenum Forage

Abstract: Revegetation and sustainable cattle grazing are major objectives in the reclamation of mine tailings at the Highland Valley Copper mine in British Columbia, Canada. A total of 84 cow-calf pairs grazed forage extremely high in molybdenum (Mo) for 11 weeks in the summer and fall for 3 consecutive years (1999-2001). The average stocking rate was 0.63 ha AUNT'. The animals' diet consisted primarily of alfalfa (Medicago sativa L.) and orchardgrass (Dactylis glomerata L.) containing 100-400 ppm Mo. Both cows and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Mining can also result in excess Mo in the soil, and forages grown on reclaimed land may be very high in Mo (Gardner et al 2003;Raisbeck et al 2006). Most cases of molybdenosis have been reported in grazing cattle because high Mo plant material is more likely to cause toxicity in cattle when eaten fresh as compared with stored (Ward 1991;Majak et al 2004).…”
mentioning
confidence: 99%
“…Mining can also result in excess Mo in the soil, and forages grown on reclaimed land may be very high in Mo (Gardner et al 2003;Raisbeck et al 2006). Most cases of molybdenosis have been reported in grazing cattle because high Mo plant material is more likely to cause toxicity in cattle when eaten fresh as compared with stored (Ward 1991;Majak et al 2004).…”
mentioning
confidence: 99%
“…The study demonstrated that grazing cows were susceptible to some degree of molybdenosis (Majak et al 2004). Clinical signs of molybdenosis are much varied (Ward 1978;Swan et al 1998), but clinical evaluations at Highmont only revealed signs of lameness, manifested as a stiff shuffling gait, diarrhea, and hair-coat depigmentation (Majak et al 2004). It should be noted that lameness and diarrhea were resolved in all animals by the end of each grazing season without treatment and hair coats returned to normal by the following spring.…”
Section: Introductionmentioning
confidence: 83%
“…To determine the impact of the high-Mo forage on grazing cattle, a 3-year (1999)(2000)(2001) clinical evaluation was initially conducted at Highmont. The study demonstrated that grazing cows were susceptible to some degree of molybdenosis (Majak et al 2004). Clinical signs of molybdenosis are much varied (Ward 1978;Swan et al 1998), but clinical evaluations at Highmont only revealed signs of lameness, manifested as a stiff shuffling gait, diarrhea, and hair-coat depigmentation (Majak et al 2004).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations